Design and Simulation of a Solar Chimney PV/T Power Plant in Northwest China - Qingjun Liu; Fei Cao; Yanhua Liu; Tianyu Zhu; Deyou Liu (International Journal of Photoenergy, 2018)
A solar chimney PV/T power plant (SCPVTPP) is proposed. Mathematical models are established for the PV/T solar collector, the chimney, and the power conversion unit, respectively. Performances of the designed SCPVTPP are then simulated. The SCPVTPPs with different PV module areas are finally discussed. It is found that the PV cells hold the highest temperature in the solar collector. Temperature rise of the PV module has significant influences to its power generation. Without cooling, the PV power capacity has an average decrease of 28.71%. The contradictory influences of temperature rise and airflow cooling lead to an 11.81% decrease of the average power capacity. By adding the power generated by PVT, the total PV-related power contribution increases by 4.72%. With the increase of the solar collector ratio, the temperature rise and the wind velocity both first decrease then increase, the SCPP power productivity decreases linearly, and the PV power productivity increases linearly, whereas the PVT power productivity first increases linearly then increases superlinearly. There is a reversed solar collector ratio, exceeding which the PV generates most power. In this study, solar thermal power takes the major role when the solar PV area ratio is smaller than 0.055.